Factors associated with chronic lung disease in preterm infants. - Cooke, R W (1991)
Among 659 infants of 30 weeks' gestation or less born in a regional perinatal centre between 1983 and 1989, 195 were ventilated for four days or more and survived to 28 days, and 87 of these developed chronic lung disease. There was a sevenfold increase in the annual incidence of chronic lung disease over time. During the same period there were significant increases in the number of infants who survived, the incidence of septicaemia, and the use of parenteral lipid emulsions. Chronic lung disease was significantly associated with low birth weight, shorter gestation, duration of ventilation, vaginal delivery, sepsis, and the use of lipid. Respiratory and physiological measurements at 96 hours were significantly worse in infants who subsequently developed chronic lung disease. Initial logistic regression showed that gestation, arterial carbon dioxide tension (PaCO2), and ventilation rate at 96 hours; and birth in 1988 or 1989, were independently associated with chronic lung disease, but when septicaemia and use of lipid during the first 21 days were included, only gestational age (odds ratio 0.64, 95% confidence interval (CI), 0.49 to 0.81 for each week) and use of lipid (odds ratio 8.1, 95% CI, 2.32 to 28.0) remained significantly associated with chronic lung disease. The observed increase in incidence of chronic lung disease in this population was associated with earlier use of parenteral lipids in infants of very low gestation rather than with changes in population, survival, or ventilator treatment of respiratory distress syndrome.